2019
DOI: 10.2478/sjph-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to mental load and psychosocial risks in kindergarten teachers

Abstract: Introduction Published research studies in Central Europe have been mostly oriented toward occupational stress among schoolteachers. The aim of this study is to investigate the level of occupational stress in kindergarten teachers and to specify psychosocial risks associated with their work. Methods The study was conducted by using a Meister questionnaire and a Psychosocial risk questionnaire. The data collection was obtained from kindergarten teachers in 2017. The survey link with request was sent to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
1
13
0
3
Order By: Relevance
“…Another study showed that there is no significant correlation between psychosocial support and job satisfaction of student counsellors (Okopi and Ofole, 2014). Other studies have showed a significance effect between psychosocial factor and job performance (Benebo-Solomon, 2015;Čecho et al, 2019;Gàlvez et al, 2018). Another study revealed that psychosocial support enhances interpersonal aspect of monitoring teachers' competences (Vanderbilt, 2010).…”
Section: Psycho-social Support and Teachers Job Performancementioning
confidence: 87%
“…Another study showed that there is no significant correlation between psychosocial support and job satisfaction of student counsellors (Okopi and Ofole, 2014). Other studies have showed a significance effect between psychosocial factor and job performance (Benebo-Solomon, 2015;Čecho et al, 2019;Gàlvez et al, 2018). Another study revealed that psychosocial support enhances interpersonal aspect of monitoring teachers' competences (Vanderbilt, 2010).…”
Section: Psycho-social Support and Teachers Job Performancementioning
confidence: 87%
“…Given this prevalence in recent years, the study of burnout in the education sector has become increasingly important (Kim and Burić, 2019 ; McLean, D., et al, 2019 ; Schonfeld et al, 2019 ). Most research has pointed out the importance of burnout on teachers (Kaur and Singh, 2014 ; Yerdelen et al, 2016 ; Salmela-Aro et al, 2019 ; Schonfeld et al, 2019 ; Mäkikangas et al, 2020 ; Pyhältö et al, 2021 ), considering it as a risk for teachers (Cecho et al, 2019 ) that can affect negatively their well-being (physically and psychologically) (Mousavy, 2014 ), effective teaching (Yerdelen et al, 2016 ), the interaction with students (Travers, 2001 ), their motivation for the job (McLean, L., et al, 2019 ), absenteeism (Makhdoom et al, 2019 ), depression (Martínez-Monteagudo et al, 2019 ), insomnia (Gu et al, 2020 ), or a decrease in the capacity to give support to the students (Jennings and Greenberg, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of all these workplace characteristics, the chance of depression emerging among employees has increased ( 7 ). National and international research results underline that workplace stress causes mental and somatic problems ( 9 , 10 , 11 ). With the number of such problems increasing, prevention has become very important.…”
Section: Introductionmentioning
confidence: 99%